Non-perturbative relativistic calculations of the K-shell-vacancy production in Xe-Xe54+ collisions. (March 2015) - Kozhedub, Y S; Tupitsyn, I I; Shabaev, V M; Plunien, G; Stöhlker, Th
Abstract: Non-perturbative calculations of the relativistic quantum dynamics of electrons in the Xe-Xe 54+ collisions at 30 AMeV are performed. The calculations are based on an independent-electron model and use the coupled-channel approach with atomic-like Dirac-Fock-Sturm orbitals. Special attention is paid to the inner-shell processes. The role of the relativistic and many-particle effects is studied.